On Almost Countably Compact of Bitopological Spaces Ali Karim Lelo Alobaidi - Ali Karim Lelo Alobaidi (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper we  introduce  the  notion  of almost countably compact spaces in bitopological spaces , give new definitions , and study some of the important properties related to this concept , the relationship between almost countably compact spaces and countably compact spaces.